2021
DOI: 10.1177/1403494821993718
|View full text |Cite
|
Sign up to set email alerts
|

The association between perceived social support in adolescence and positive mental health outcomes in early adulthood: a prospective cohort study

Abstract: Aims: The link between perceived social support and mental health has received much attention from numerous scientific fields in recent years. Most studies, however, have examined associations only over relatively short follow-up periods using global measures of perceived social support and dichotomous negative indicators of mental health. We investigated the long-term association between perceived social support from friends, parents and teachers and multiple positive hedonic and eudemonic indicators of menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…Furthermore, it has been found to alleviate anxiety, depression, and loneliness, with more perceived social support leading to better mental health ( Grey et al, 2020 ). Evidence documents that high levels of perceived social support promote mental health at all points in life ( Barker, 2007 ; Pinkerton and Dolan, 2007 ; Jakobsen et al, 2021 ). Thereby, the literature proposes that the more social support - received or perceived - a person has, the more they feel in control and the better they are able to cope with difficult situations, in particular ( Szkody et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been found to alleviate anxiety, depression, and loneliness, with more perceived social support leading to better mental health ( Grey et al, 2020 ). Evidence documents that high levels of perceived social support promote mental health at all points in life ( Barker, 2007 ; Pinkerton and Dolan, 2007 ; Jakobsen et al, 2021 ). Thereby, the literature proposes that the more social support - received or perceived - a person has, the more they feel in control and the better they are able to cope with difficult situations, in particular ( Szkody et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed within a variable-centered approach whether educational and health concerns and perceived social support predicted adolescents’ mental health, reflected in their current well-being and depressive mood. Similar to the hypotheses regarding the resilience profiles, we assumed negative associations between educational and health concerns with mental health and positive associations of all sources of perceived social support with adolescents’ mental health (e.g., Grey et al, 2020 ; Bernasco et al, 2021 ; Bray et al, 2021 ; Jakobsen et al, 2021 ; van Loon et al, 2021 ; Ye et al, 2021 ). Regarding the relative role of educational and health concerns, we investigated whether these predictors differed in their association with both aspects of mental health.…”
Section: Introductionmentioning
confidence: 99%
“…High perceived social support during adolescence is associated with positive concurrent outcomes, including better mental health, academic achievement, social adjustment, and psychological well-being (Heerde & Hemphill, 2018; Chu et al, 2010). Longitudinal studies have also shown that perceived support during adolescence is associated with positive psychosocial outcomes in adulthood, such as fewer depressive symptoms (Needham, 2008), increased health-promoting behaviors (Frech, 2012), and more positive mental health indicators (Jakobsen et al, 2021). Social support in adolescence can come from parents but also from many people outside of the home, including peers, teachers, and adult mentors.…”
mentioning
confidence: 99%
“…Ecobiodevelopmental theory proposes that both family and nonfamily members are important sources of stable and growth-promoting relationships as well as critical buffers against significant threats to healthy development (Shonkoff, 2010). Moreover, a wealth of studies have indicated that perceived social support is an important protective factor during child and adolescent development (Amin et al, 2021;Glozah & Pevalin, 2014;Jakobsen et al, 2021;Peter et al, 2017;Rueger et al, 2016).…”
Section: The Potential Moderating Role Of Perceived Social Supportmentioning
confidence: 99%